Reducing Disorder, Fear, and Crime in Public Housing: Evaluation of a Drug-Crime Elimination Program in Spokane, Washington, 1992-1995 - McGarrell, Edmund ([Verlag nicht ermittelbar], 2000)
Established in 1994, Project ROAR (Reclaiming Our Area Residences) is a public housing drug-crime elimination program sponsored by the Spokane Police Department and the Spokane Housing Authority. This study was undertaken to examine and evaluate the effects and outcomes of Project ROAR as it was implemented in the Parsons' Public Housing Complex, located in downtown Spokane, Washington. In addition, the study sought to determine to what extent the project as implemented reflected Project ROAR as originally conceived, and whether Project ROAR could be considered a comprehensive community policing crime prevention program. Further, the study attempted to determine what effects this collaborative anti-crime program might have on: (1) residents' perceptions of the quality of their neighborhood life, including perceptions of neighborhood inhabitants, satisfaction with their neighborhood, fear of crime, and neighborhood physical and social disorder, (2) objective measures of physical and social disorder, (3) levels of neighborhood crime, and (4) subjective perceptions of the level and quality of policing services. To assess the implementation and short-term impacts of Project ROAR, data were collected from various sources. First, four waves of face-to-face interviews were conducted with Parsons' Public Housing residents at approximately six-month intervals: April 1994, December 1994, May 1995, and November 1995 (Part 1, Public Housing Residents Survey Data). Information collected from interviews with the Parsons' residents focused on their involvement with Project ROAR, community block watches, and tenant councils. Residents commented on whether there had been any changes in the level of police presence, drug-related crimes, prostitution, or any other physical or social changes in their neighborhood since the inception of Project ROAR. Residents were asked to rate their satisfaction with the housing complex, the neighborhood, the Spokane Police Department, the number of police present in the neighborhood, and the level of police service. Residents were also asked if they had been the victim of any crimes and to rate their level of fear of crime in the complex during the day and night, pre- and post-Project ROAR. The gender and age of each survey participant was also recorded. The second source of data was a city-wide survey mailed to the residents of Spokane (Part 2, Spokane Citizens Survey Data). Information collected from the survey includes demographics on ethnicity, gender, age, highest level of education, present occupation, and family income. The city residents were also asked to assess the level of police service, the number of police present in their neighborhood, the helpfulness of neighbors, whether they felt safe alone in their neighborhood, and overall satisfaction with their neighborhood. Third, a block-level physical and social disorder inventory was taken in April 1994, October 1994, April 1994, and October 1995 (Part 3, Neighborhood Inventory Data). The sex, age, and behavior of the first ten people observed during the inventory period were recorded, as well as the number of people observed loitering. Other observations made included the number of panhandlers, prostitutes, open drug sales, and displays of public drunkenness. The number of residential and commercial properties, restaurants, bars, office buildings, empty lots, unboarded and boarded abandoned buildings, potholes, barriers (walls or fences), abandoned cars, and for-sale signs, along with the amount of graffiti on public and private properties and the amount of litter and broken glass observed in each neighborhood, completed the inventory data. Finally, crime reports were collected from the Spokane Police Department's Crime Analysis Unit (Part 4, Disaggregated Crime Data, and Part 5, Aggregated Crime Data). These data contain monthly counts of robberies and burglaries for the public housing neighborhood, a constructed controlled comparison neighborhood, and the city of Spokane for the period January 1, 1992, through December 31, 1995.